2020
DOI: 10.1021/acssuschemeng.0c04078
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layered Phosphorene–Graphitic Carbon Nitride Nanoheterostructure as a Metal-Free Photocatalyst for Aerobic Oxidation of Benzyl Alcohol and Toluene

Abstract: Herein, we have, for the first time, fabricated a few-layered phosphorene (FLP) and few-layered carbon nitride (FLCN) nanoheterostructure as a metal-free and broad solar light-absorbing photocatalyst for highly selective conversion of primary C–H bond of toluene and benzyl alcohol to benzaldehyde in the presence of oxygen. The FLP–FLCN photocatalyst can effectively oxidize benzyl alcohol to benzaldehyde with superior selectivity (>99%) under the visible light irradiation conditions. Moreover, a conversion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…OH, and . O 2− , respectively [47,48] . As shown in Figure 9, it can be found that the degradation efficiency of ZnO‐GO‐1 decreases with the addition of capture agent and the photocatalytic efficiency decreased from 98.93 % (100 min) to 44.23 % (100 min), 50.12 % (100 min), and 52.67 % (100 min) in the presence of IPA, KI, and N 2 , respectively.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…OH, and . O 2− , respectively [47,48] . As shown in Figure 9, it can be found that the degradation efficiency of ZnO‐GO‐1 decreases with the addition of capture agent and the photocatalytic efficiency decreased from 98.93 % (100 min) to 44.23 % (100 min), 50.12 % (100 min), and 52.67 % (100 min) in the presence of IPA, KI, and N 2 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…1 mmol KI, 1 mmol IPA and N 2 were added into the MO solution as the scavengers of the h + , * OH, and * O 2À , respectively. [47,48] As shown in Figure 9, it can be found that the degradation efficiency of ZnO-GO-1 decreases with the addition of capture agent and the photocatalytic efficiency decreased from 98.93 % (100 min) to 44.23 % (100 min), 50.12 % (100 min), and 52.67 % (100 min) in the presence of IPA, KI, and N 2 , respectively. The result of the catalytic degradation shows that * OH, h + , and * O 2À play the important role in the process of degrading MO and ZnO-GO-1 can generate more * OH to photocatalytic degrade dyes.…”
Section: Photocatalytic Mechanismmentioning
confidence: 90%
“…Several graphitic carbon nitrides were also employed as photocatalysts in the transformation of alcohols to aldehydes or ketones. Thus, a carbon-nanodot-doped material derived from 33 [193], a few-layered phosphorene nanostructure graphitic material [194], the basic unmodified graphitic carbon nitride 33 [119,195,196] and several 33 modified by thermal, chemical and mechanical processes [197], with N vacancies [198] and doped with P [199], O [200] and S atoms [201], could successfully catalyze the mentioned reaction under visible light irradiation. The photocatalysts were able to be reused after centrifugation or filtration without decreasing their catalytical activity.…”
Section: Heterogeneous Oxidative Dehydrogenation Of C-o Bondmentioning
confidence: 99%
“…Alkoxide radicals are produced from alkoxide anions when they come into contact with a photogenerated hole. Then, the alkoxide reacts with another • O 2− and hole, releasing another proton from the hydroxymethyl moiety and forming a carbon radical [54].…”
Section: Photocatalytic Oxidation Of Benzyl Alcoholmentioning
confidence: 99%